'Howzat'—how do artefacts without matter, matter? The case of decision review systems in professional cricket. (July 2017) - McLoughlin, Ian; Dawson, Patrick
Abstract : It has been argued that the social and material worlds are increasingly entangled as they become mediated by and experienced through virtual representations of live events. Virtual decision review systems in professional sport provide an albeit unusual case study example of such developments where virtual (re‐)representations of events are increasingly used in match play to inform adjudicator decisions concerning 'what really happened'. This has prompted an ongoing debate in many sports over both the accuracy and appropriateness of these technologies for representing events which are often fast moving and difficult to judge with the human eye. We explore these issues using a sociomaterial practice lens and indicate the broader relevance of the case for basing judgements and decisions on virtual views of reality.